Currency Appreciation as an Anti-Inflationary Device: Further Comment - Hirschman, Albert O. (Quarterly Journal of Economics, 1952)
Journal Article Currency Appreciation as an Anti-Inflationary Device: Further Comment Get access Albert O. Hirschman Albert O. Hirschman Washington, D. C. Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 66, Issue 1, February 1952, Pages 117–120, https://doi.org/10.2307/1882080 Published: 01 February 1952